Peningkatan Kompetensi Abstraksi dan Dekomposisi Computational Thinking Melalui LKPD Digital dan Card Mat Modular bagi Guru SMPN 1 Baleendah - Gelar, Trisna; Firdaus, Lukmannul Hakim; Rullyana, Gema (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance the pedagogical competence of teachers at State Junior High School 1 Baleendah in applying the concepts of Abstraction and Decomposition in Computational Thinking (CT) within the learning process, while improving operational efficiency in managing teaching materials through the utilization of structured digital systems and media. The program was implemented using a participatory approach with an integrated hybrid intervention. The effectiveness of the intervention was evaluated using a one-group pretest-posttest design with cognitive understanding tests and rubric-based performance observation sheets, which were subsequently analyzed using descriptive quantitative methods. The results showed that the hybrid model was effective in overcoming pedagogical barriers, as evidenced by a significant improvement in conceptual understanding and the quality of CT implementation in learning activities, with an average post-test score increase of 15%. In addition, operational inefficiency was addressed through improved time efficiency in preparing teaching materials, reaching an increase of at least 60%. This model also generated findings regarding the effectiveness of Hexagon Chips as cognitive artifacts for mediating the visualization of the concepts of Abstraction and Decomposition in Computational Thinking.